2012
DOI: 10.3390/s120506282
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Representing Sensor Data to Validate Alerts in Ambient Assisted Living

Abstract: The mainstream of research in Ambient Assisted Living (AAL) is devoted to developing intelligent systems for processing the data collected through artificial sensing. Besides, there are other elements that must be considered to foster the adoption of AAL solutions in real environments. In this paper we focus on the problem of designing interfaces among caregivers and AAL systems. We present an alert management tool that supports carers in their task of validating alarms raised by the system. It generates text-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Based on user needs and with the aim of improving alert handling, [10] does have a representation of functionality as an algorithm description, and contextual information is also displayed. It does have two case studies with which requirements are validated and their argumentation explanation is shown and applied.…”
Section: Related Workmentioning
confidence: 99%
“…Based on user needs and with the aim of improving alert handling, [10] does have a representation of functionality as an algorithm description, and contextual information is also displayed. It does have two case studies with which requirements are validated and their argumentation explanation is shown and applied.…”
Section: Related Workmentioning
confidence: 99%
“…Some works have got deep into this aspect, highlighting the importance of such events, not only from the user needs perspective, but also from its critical handling and interface information displaying [25,26]. Design in [25] attends specifically the interfaces for interaction between carers and the AAL system, showing the importance of giving support to carers on checking the situations inferred by the system (alerts, subject's location and activities, etc .) in a friendly and intuitive manner [27], including the availability of explanations for such situations, both textual and visual.…”
Section: Introductionmentioning
confidence: 99%
“…Agents pose advantages for the development of AAL systems [21,10,15]. However, current solutions do not allow the development of heterogenous MAS, because they are restricted to a single agent platform and network technology [21], which makes difficult the integration of new technologies.…”
Section: Our Approachmentioning
confidence: 99%
“…In this case, agents are used to observe the elderly person from various points of view. An argumentative MAS is used in [15] to enable the reproduction and evaluation of inconsistent situations detected by AAL systems. They are part of an alarm management tool that supports carers to validate alarms raised by AAL systems.…”
Section: Related Workmentioning
confidence: 99%